Inquiry Based Colage Activities Using Colored Shells on The Development of Creativity of Early Children - Rakimahwati Rakimahwati; Nazifa 'Aisy; Eka Pentiernitasari; Yulsyofriend Yulsyofriend; Indrayeni Indrayeni; Sri Hartati; Amalia Husna; Nisaul Hanifah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The development of children's creativity has not developed optimally, this can be seen from children's activities in generating new ideas and problem solving that have not been seen. The purpose of this study was to determine the effect of inquiry-based collage activities using colored shells on the development of early childhood creativity. This type of research uses quantitative methods with a quasi-experimental design. The population in this study were all students in Adzkia Air Bangis Kindergarten with a sample of 60 students which included 30 students in B1 and 30 students in B2. Data collection techniques in this study is by observation. The data analysis technique used normality test, homogeneity test and hypothesis testing, namely the independent sample test. Based on the results of this study, it was found that in the normality test the data were normally distributed with a significant value of Kolmogrov-Smirnov in each class, namely 0.05. In the homogeneity test, it was found that the value based on the mean was 0.789 0.05, which means the data is homogeneous. Meanwhile, in hypothesis testing, the value of sig (2 tailed) is 0.001 0.05. Thus, it can be concluded that inquiry-based collage activities using colored shells have an effect on the development of creativity in early childhood